Pengaruh Penggunaan Metode Magic Story Terhadap Penguasaan Mufrodat Siswa Kelas VIIB MTs Darul Masholeh Cirebon - Saliqul Saliqul Abror; Wawan Arwani; Khasan Aedi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
This study aims to determine the ability of students to master vocabulary in learning Arabic without using the Magic Story technique, determine the ability of students to master vocabulary in learning Arabic by using the Magic Story technique, and determine the effect of using the Magic Story technique on students' vocabulary mastery in language learning Arabic in Class VII B at MTs Darul Masholeh. In this study, researchers used a quantitative approach to the experimental design. Data collection techniques are direct observation, tests and interviews. The data analysis techniques used in this study are normality test, homogeneity test, and hypothesis increase in high scores. Student scores on prestest obtained the lowest value of 33, the median of 53, the highest value of 73 with a mean or an average of 52 testing. The results of the study in this thesis are (1) the ability of students to master the mastery of mufrodat before using the Magic Story Technique there is no.74; (2) The ability of students towards mastery of mufrodat by using the Magic Story Technique there is a high increase in grades. Student scores on the posttest obtained the lowest value of 73, a median of 80, the highest value of 93 with a mean or an average of 80.37; (3) The effect of the use of the Magic Story technique on students' mastery of mufrodat Based on the results of the regression test above a significant value of 0,000 and t arithmetic of 4.357. Because the significant value is smaller than 0.05 and t arithmetic (4.357) is greater than t table (1.70814) then Ho is rejected, meaning that there is an influence of the use of magic story techniques on mastery of students.